2019
DOI: 10.1186/s12889-019-7755-4
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence of burnout and associated factors among general practitioners in Hubei, China: a cross-sectional study

Abstract: BackgroundHigh occupational burnout among general practitioners (GPs) is an important challenge to China’s efforts to strengthen its primary healthcare delivery; however, data to help understand this issue are unavailable. This study aimed to investigate the prevalence of burnout and associated factors among GPs.MethodsA cross-sectional design was used to collect data from December 12, 2014, to March 10, 2015, with a self-administered structured questionnaire from 1015 GPs (response rate, 85.6%) in Hubei Provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
7
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 39 publications
2
51
7
11
Order By: Relevance
“…This increase in experienced workload of PC providers may lead to burnout. The prevalence of moderate burnout in this study (47.1%) is much lower than that (70.25%) shown by a recent published study from Hubei Province, China [26], which may be due to the study scale (national vs. regional) or the different instruments adopted (MBI-GS vs. MBI-HSS) to measure burnout. The results of this current study demonstrated that the prevalence of reduced personal accomplishment was higher than that of the other two subcomponents, which is in line with the results of previous studies conducted at Chinese PC facilities [19,26,33].…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…This increase in experienced workload of PC providers may lead to burnout. The prevalence of moderate burnout in this study (47.1%) is much lower than that (70.25%) shown by a recent published study from Hubei Province, China [26], which may be due to the study scale (national vs. regional) or the different instruments adopted (MBI-GS vs. MBI-HSS) to measure burnout. The results of this current study demonstrated that the prevalence of reduced personal accomplishment was higher than that of the other two subcomponents, which is in line with the results of previous studies conducted at Chinese PC facilities [19,26,33].…”
Section: Discussioncontrasting
confidence: 88%
“…The prevalence of moderate burnout in this study (47.1%) is much lower than that (70.25%) shown by a recent published study from Hubei Province, China [26], which may be due to the study scale (national vs. regional) or the different instruments adopted (MBI-GS vs. MBI-HSS) to measure burnout. The results of this current study demonstrated that the prevalence of reduced personal accomplishment was higher than that of the other two subcomponents, which is in line with the results of previous studies conducted at Chinese PC facilities [19,26,33]. Reported low levels of personal accomplishment among Chinese PC providers might be explained by the fact that citizens are free to choose their first-contact health care facility; they generally have little trust in PC and usually bypass PC facilities to seek health care in hospitals [19].…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…The possible interpretation for the high-level turnover intention among Chinese primary care providers is their heavy workload, low income level, and few professional development opportunities [15]. Moreover, 11.3% of participants reported severe burnout, which was higher than that reported among Chinese primary care doctors [34] and primary care providers in the US [35]. The mean score for social support in this study was 64.93, which was lower than reported in a previous study involving Chinese physicians [25].…”
Section: Discussionmentioning
confidence: 89%
“…The prevalence of academic burnout differs worldwide [7][8][9]. It often occurs as the result of inability to cope with the educational curriculum [10][11][12].…”
Section: Introductionmentioning
confidence: 99%